Minimasi Maskepan Dengan Penjadwalan Produksi Pada Tipe Produksi Berulang - Imron Kuswandi (Jurnal Teknik Industri, 2010)
Methodologically there are some problems in the methods of scheduling production whichhave been available. In the methods of scheduling production which have been available, it isoften less capable for giving the real condition images from the real systems. It is indicated bythe given assumption that each operation should be finished previously before the other operationsare done. This case is inappropriate if applied in the repetitive production types as happenedin X Gresik, Co. Ltd. Because methodologically there are some problems in the methodsof scheduling conventional production, so in this research the methods of scheduling conventionalproduction are modified by using Microsoft excel application software, so it enables inthis method to handle the case of scheduling production in the types of repetitive production.urthermore, by using the methods of scheduling production modified by using Microsoft excelapplication software, the scheduling can be achieved by the better makespan (makespan =471,17 hours), so the production facility utilities are also more optimal compared to productionscheduling results by conventional approach (makespan = 893,7 hours).